Synthesis of a deuterated 6‐AmHap internal standard for the determination of hapten density in a heroin vaccine drug product. (28th September 2020) - Makarova, Mariia; Barrientos, Rodell C.; Torres, Oscar B.; Matyas, Gary R.; Jacobson, Arthur E.; Sulima, Agnieszka; Rice, Kenner C.
Abstract : A deuterated hapten was designed and synthesized that will be essential for a future study of residual hapten and stability of a hapten‐protein conjugate. This hapten, 6‐AmHap, was chosen for a heroin vaccine that is now slated for a Phase 1 clinical trial. A maleimide‐thiol bioconjugation strategy was successfully applied to our heroin vaccine to connect the hapten 6‐AmHap with an immunogenic carrier protein (tetanus toxoid, TT) through a trityl‐protected 3‐mercaptopropanamide linker. The antibodies induced by the vaccine have been found to have activity against several opioids, including heroin and its metabolites, and, importantly, leave alternate pain treatment medications such as methadone untouched. To the best of our knowledge, no other hapten for a heroin vaccine has been deuterated, yet this tool may prove to be of great importance in the study of residual hapten during product release and the long‐term stability program of a hapten‐protein conjugate as part of FDA regulatory requirements. Hydrocodone was the starting material for the synthesis of the deuterated 6‐AmHap, with a stable amide at C6 and a 3‐mercaptopropanamide linker attached at C3. The desired deuterated product was prepared as the disulfide, 3, 3′‐disulfanediylbis( N ‐((7 S, 7a R, 12b S )‐7‐acetamido‐3‐[ 2 H3 ]methyl)‐2, 3, 4, 4a, 5, 6, 7, 7a‐octahydro‐1 H ‐4, 12‐methanobenzofuro[3, 2‐ e ]isoquinolin‐9‐yl)propanamide), that could be easily reduced to form the needed hapten, N ‐((4a R, 7 S, 7a R, 12b S )‐7‐acetamido‐3‐[ 2 H3 ]methyl]‐2, 3, 4, 4a, 5, 6, 7, 7a‐octahydro‐1 H ‐4, 12‐methanobenzofuro[3, 2‐ e ]isoquinolin‐9‐yl)‐3‐mercaptopropanamide. Abstract : An eight‐step synthesis provided the stable disulfide of the deuterated 6‐AmHap (9 ) in 10% overall yield and deuterium incorporation of 97.6%.